2019
DOI: 10.1038/s41598-019-52727-z
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant DNA methylation of miRNAs in Fuchs endothelial corneal dystrophy

Abstract: Homeostatic maintenance of corneal endothelial cells is essential for maintenance of corneal deturgescence and transparency. in fuchs endothelial corneal dystrophy (fecD), an accelerated loss and dysfunction of endothelial cells leads to progressively severe visual impairment. An abnormal accumulation of extracellular matrix (ecM) is a distinctive hallmark of the disease, however the molecular pathogenic mechanisms underlying this phenomenon are not fully understood. Here, we investigate genome-wide and sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 98 publications
0
29
2
Order By: Relevance
“…Lack of the TCF4 genotype and different filtering methods in previous FECD methylation studies could be one of the reasons why there is not much agreement in our results compared to Khuc et al [34] and Pan et al [25] who used Illumina 450K methylation array without genotyping TCF4. We used a different method to calculate significant changes between FECD and controls; β-values versus M-values and an absolute difference versus linear model, which could also bring the dissimilarities.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Lack of the TCF4 genotype and different filtering methods in previous FECD methylation studies could be one of the reasons why there is not much agreement in our results compared to Khuc et al [34] and Pan et al [25] who used Illumina 450K methylation array without genotyping TCF4. We used a different method to calculate significant changes between FECD and controls; β-values versus M-values and an absolute difference versus linear model, which could also bring the dissimilarities.…”
Section: Discussioncontrasting
confidence: 69%
“…A well-known consequence of DNA methylation at gene promoter regions is gene silencing, whereas gene body methylation may be involved in the regulation of gene splicing [32,33]. DNA methylation patterns in CE tissue from FECD patients with unknown TCF4 status have been investigated earlier, revealing altered methylation of promoter regions in FECD patients compared to controls [25,34]. However, the effect of an expanded CTG18.1 locus on methylation in FECD remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…2015; Pan et al. 2019), repeat‐associated non‐ATG translation (Soragni et al. 2018) and hypermethylation in the corneal endothelium (Khuc et al.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al indicated that the high degree of miR-199b-5p methylation may be related to the pathogenesis of FECD. They confirmed that miR-199b-5p directly targets the 3′-UTR of SNAI1 and ZEB1 transcripts and represses their expression and link the downregulation of miR-199b-5p by its methylation to the upregulation of both SNAI1 and ZEB1 [ 48 ]. Riazuddin et al reported a pathogenic mutation of ZEB1 in FECD, but other studies have not shown a significant correlation between ZEB1 and the disease [ 49 ].…”
Section: Zeb1 and Corneal Endotheliummentioning
confidence: 91%